2007
DOI: 10.1080/10942910601048911
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Sensory Changes in Minced Beef Treated with Potassium Lactate and Sodium Diacetate during Refrigerated Storage

Abstract: The effect of potassium lactate and sodium diacetate on the microbiological changes and sensory properties of vacuum-packaged minced beef was investigated. The meat samples both with a preservative (in the amounts 0.65% and 1.3%) and without were stored at temperatures of 0-1°C and 5-6°C. The influence of storage time on changes in total bacteria count (TBC), lactic acid bacteria (LAB), Brochothrix thermosphacta, and the microbes of the Enterobacteriaceae family was investigated, as well as changes in pH and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Strains of LAB can produce fermentation products in the form of organic acids which may result in a decrease in pH over time (Jones, 2004;Sakala et al, 2002). LAB strains of bacteria are known to be resistant to many antimicrobial substances (Han et al, 2014;Fik & Leszczyska-Fik, 2007;Emiroğlu et al 2010). In our study, we observed the successful growth of LAB in our antimicrobially-treated packs (see next section for greater detail).…”
Section: Ph Values Of Packaged Beef Steakssupporting
confidence: 56%
“…Strains of LAB can produce fermentation products in the form of organic acids which may result in a decrease in pH over time (Jones, 2004;Sakala et al, 2002). LAB strains of bacteria are known to be resistant to many antimicrobial substances (Han et al, 2014;Fik & Leszczyska-Fik, 2007;Emiroğlu et al 2010). In our study, we observed the successful growth of LAB in our antimicrobially-treated packs (see next section for greater detail).…”
Section: Ph Values Of Packaged Beef Steakssupporting
confidence: 56%
“…the period during which the samples maintained good quality and usability, 5 next decreased slightly and then on the 22nd day grew significantly (P < 0.05) again. In the control samples, however, after a significant quantitative growth of this component in the first 6 days, the amino nitrogen content decreased and it showed a tendency towards some quantity fluctuations during further storage.…”
Section: Results and Discussion Proteolytic Activitymentioning
confidence: 84%
“…The increase in proteolytic activity resulting from extended refrigerated storage could also be the result of progressing microbial contamination of ground beef. 5 During storage at the temperature of 0-1…”
Section: Results and Discussion Proteolytic Activitymentioning
confidence: 99%
See 2 more Smart Citations